1988
DOI: 10.1016/0039-6257(88)90070-7
|View full text |Cite
|
Sign up to set email alerts
|

Corneal hypoesthesia

Abstract: Decreased corneal sensitivity is an important clinical parameter in neuro-ophthalmological evaluation. It may be associated with such disorders as diabetes, Herpes simplex keratitis, and myasthenia gravis, with corneal toxicity via chemical exposure or ocular drug therapy, and with ocular surgery. In this review, methods and precautions involved in measuring corneal sensitivity are summarized, and the clinical conditions in which corneal hypoesthesia may exist are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
1
4

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(52 citation statements)
references
References 95 publications
1
46
1
4
Order By: Relevance
“…neuropathies, congenital abnormalities) conditions may also cause corneal hypoesthesia. 9 The 1980 report 12 showing good correlation of esthesiometry and DR stage described only 37 patients. Despite showing good differentiation between groups at the ends of the DR severity spectrum (NoDR and PDR), the author did not make considerations on patients in intermediate positions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…neuropathies, congenital abnormalities) conditions may also cause corneal hypoesthesia. 9 The 1980 report 12 showing good correlation of esthesiometry and DR stage described only 37 patients. Despite showing good differentiation between groups at the ends of the DR severity spectrum (NoDR and PDR), the author did not make considerations on patients in intermediate positions.…”
Section: Discussionmentioning
confidence: 99%
“…For that reason the predictive val- The methods of measuring corneal esthesiometry and staging DR were chosen based on the availability in the Brazilian public health system. 10 For corneal esthesiometry the Cochet-Bonnet esthesiometer is considered the standard method 9 and aside from being the most used instrument for that purpose is also an easy to handle device.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Millodot found that subjects with blue irides exhibited significantly more sensitive corneas than subjects with brown irides, and that sensitivity is lower in nonwhite subjects with darker pigmented eyes compared with whites with darker pigmented eyes. [81][82][83] In a more recent study comparing LASIK-induced dry eye symptoms between Asians and Caucasians, corneal sensation at 3 and 6 months post-LASIK decreased more in Asians compared with whites. 80 If Asians have innately lower corneal sensitivity, then why do Asians report more dryness and discomfort during contact lens wear?…”
Section: Symptomatology: Dryness and Discomfort With Contact Lens Wearmentioning
confidence: 99%
“…The cornea is one of the regions of the human body that has the highest amount of naked nerve endings and, therefore, has a high level of pain sensitivity. The sensory innervation of the cornea is essential in maintaining corneal integrity (9,10) . The touch sensitivity threshold of the cornea, particularly in the center, is rather low.…”
Section: Introductionmentioning
confidence: 99%